Muscle-derived stem cell exosomes with overexpressed miR-214 promote the regeneration and repair of rat sciatic nerve after crush injury to activate the JAK2/STAT3 pathway by targeting PTEN - Zeng, Xiangyu; Bian, Wei; Liu, Ziwen; Li, Jianming; Ren, Shuai; Zhang, Jian; Zhang, Haoran; Tegeleqi, Bu; He, Guanyi; Guan, Mingyan; Gao, Zewei; Huang, Chi; et al. (Frontiers in Molecular Neuroscience, 2023)
Introduction This study aimed to investigate the effect of muscle-derived stem cell (MDSC) exosomes with overexpressed miR-214 on the regeneration and repair of rat sciatic nerve after crush injury and its molecular mechanism. Methods First, primary MDSCs, Schwann cells (SCs) and dorsal root ganglion (DRG) neurons were isolated and cultured, and the characteristics of MDSCs-derived exosomes were identified by molecular biology and immunohistochemistry. NC mimics and miR-214 mimics were transfected to obtain exo-NC and exo-miR-214. An in vitro co-culture system was established to determine the effect of exo-miR-214 on nerve regeneration. The restoration of sciatic nerve function of rats by exo-miR-214 was evaluated by walking track analysis. Immunofluorescence for NF and S100 was used to detect the regeneration of axon and myelin sheath in injured nerve. The Starbase database was used to analyze the downstream target genes of miR-214. QRT-PCR and dual luciferase reporter assays were used to validate the miR-214 and PTEN interaction relationship. And the expression of the JAK2/STAT3 pathway-related proteins in sciatic nerve tissues were detected by western blot. Results The above experiments showed that MDSCs-derived exosomes with overexpressed miR-214 was found to promote the proliferation and migration of SCs, increase the expression of neurotrophic factors, promote axon extension of DRG neurons and positively affect the recovery of nerve structure and function. In addition, PTEN was a target gene of miR-214. Exo-miR-214 can significantly inhibit the expression level of PTEN, increase the protein expression levels of p-JAK2 and p-STAT3 and the ratio of p-JAK2/JAK2 and p-STAT3/STAT3, also MDSCs-derived exosomes with overexpressed miR-214 can reduce the occurrence of denervated muscle atrophy. Conclusion In summary, the MDSCs-derived exosomes with overexpressed miR-214 is involved in peripheral nerve regeneration and repair in rats after sciatic nerve crush injury to activate the JAK2/ STAT3 pathway by targeting PTEN.